Your UNIX/LINUX the ultimate guide - Das, Sumitabha (McGraw-Hill, 2013)
Suitable for both users and programmers, this UNIX/Linux text features a pedagogical framework that allows beginning students to gain a grasp of fundamental concepts. It also features chapters on advanced topics that inspire experienced reader to move beyond the basics.